Responses of liquid organic fertilizer application of shallots to the growth of various types of mustard plants - Fibriani, Suwinda; Krismiratsih , Fitri (KHD Production, 2025)
Mustard greens (Brassica sp.) are one of the horticultural plants widely cultivated by the community. Mustard production can be increased through fertilization activities. Mustard plants require balanced soil nutrients such as nitrogen, phosphorus, and potassium (N, P, K) to support optimal growth. Liquid organic fertilizer (POC) has been developed to reduce dependence on the use of inorganic fertilizers. POC made from shallots contains complete macro and micronutrients that can be utilized by mustard plants for optimal growth. This research aims to study the response of liquid organic fertilizer (POC) from shallots on the growth of various types of mustard greens. The research was conducted at the Jember State Polytechnic from June to August 2024, using a Factorial Randomized Block Design (RBD) with 3 replications, involving POC concentrations of 0, 20, 40, and 60 ml/L on the mustard varieties Pakcoy, Samhong, Pagoda, and Caisim. The results showed that the 60 ml/L POC concentration significantly increased the number of leaves and plant height in Samhong and Pagoda mustard greens at 40 days after planting.